Satellite In-Orbit Secondary Collision Risk Assessment - Haicheng Tao; Xueke Che; Qinyu Zhu; XinHong Li (International Journal of Aerospace Engineering)
The massive mega constellation of satellites will have a significant impact on global space safety. With Starlink as an example, this paper is aimed at assessing the risk of in-orbit collision, analyzing the probability of collision in orbit in its natural operating state, and forecasting the probability of secondary collision between the collision-generated short-term debris cloud and satellites in the same orbit. The mass, size, velocity, and direction of space debris in a particular orbit of Starlink satellite are calculated based on the MASTER-8 model, and the shape characteristics of the Starlink satellite are added to the model to determine the probability of a Starlink satellite colliding with space debris in that orbit. A modified spacecraft impact disintegration model then is used to calculate the collision results and estimate the collision threat level of the short-term debris cloud formed by the Starlink satellite after its destruction to satellites in the same orbit. The results indicate that the collision probability of Starlink satellite in orbit natural operation exceeds the red warning threshold 10-4 that the satellite disintegration after the first collision will generate 14088 pieces of debris over 1 cm, of which 4092 debris are potentially dangerous to other spacecraft, and that the collision probability to a satellite in the same orbit exceeds the red warning threshold of 10-4 within 30 minutes, implying that collision avoidance needs to be improved.